Addressing the Rural Context in Literacies Research: A Call to Action. Issue 3 (November 2015) - Azano, Amy Price
Abstract: The article features a discussion about rural contexts in literacy research. Rural students compose a significant portion of K–12 students, and rural schools have unique challenges, such as limited funding and resources. However, as a field of literacy researchers, we do not privilege place equitably across multiple contexts. The article serves as a call to action for literacy researchers and educators to promote greater social justice and address educational inequities for rural students.